Most effective method for the management of physiologic gingival hyperpigmentation: A systematic review and meta-analysis - Meisha Gul; Muhammad Hasan Hameed; Muhammad Rizwan Nazeer; Robia Ghafoor; Farhan Raza Khan (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: Gingival hyperpigmentation is an esthetic problem. The aim of the present study was to identify most effective treatment modality for managing generalized physiological gingival pigmentation. Materials and Methods: A systematic review and meta-analysis were done (1919 to October 2018) using PubMed, CINHAL, Dental and Oral Science, and manual searches. Twenty-five articles were finally reviewed. Only human clinical trials were considered with physiological gingival pigmentation treated with different depigmentation methods and compared with surgical stripping. The outcome was the achievement of gingival depigmentation and its recurrence. RevMan software was used for data analysis. Results: Of 26,132 articles, 25 met the inclusion criteria. Seventeen were randomized control trials and 8 were nonrandomized control trials. Most of the studies were on laser. The control group was scalpel surgery. Majority of studies showed no difference in compared treatment modality. A meta-analysis compared laser ablation with surgical stripping revealed a nonsignificance difference regarding recurrence (P = 0.75) and depigmentation (P = 0.23) and a statistically significant difference regarding postoperative pain favoring laser ablation (P ≤ 0.05). Conclusions: Surgical stripping has been the conventional treatment of choice, but our review showed that new techniques are equally effective or even better. Laser especially diode laser was the most frequently used technique and showed better esthetic outcomes, less pain, faster healing, and patients' preference and satisfaction after treatment. However, laser showed more regimentation at 6-month evaluation. More good quality randomized controlled trials with different depigmentation methods are needed to draw strong conclusions.